Amorphous-crystalline transition in thermoelectric NbO2. (9th June 2015) - Music, Denis; Chen, Yen-Ting; Bliem, Pascal; Geyer, Richard W
Abstract: Density functional theory was employed to design enhanced amorphous NbO2 thermoelectrics. The covalent-ionic nature of Nb–O bonding is identical in amorphous NbO2 and its crystalline counterpart. However, the Anderson localisation occurs in amorphous NbO2, which may affect the transport properties. We calculate a multifold increase in the absolute Seebeck coefficient for the amorphous state. These predictions were critically appraised by measuring the Seebeck coefficient of sputtered amorphous and crystalline NbO2 thin films with the identical short-range order. The first-order phase transition occurs at approximately 550 °C, but amorphous NbO2 possesses enhanced transport properties at all temperatures. Amorphous NbO2, reaching −173 μ V K −1, exhibits up to a 29% larger absolute Seebeck coefficient value, thereby validating the predictions.